Endophytic plant growth promoting bacteria from two halophytes improve wheat performance under salt stress - He, Xuemin; Yuan, Hongfei; Li, Yan; Yang, Chen (Frontiers in Plant Science, 2026)
Plant growth-promoting endophytes (PGPE) in halophytes have the potential to enhance plant stress resistance and promote growth, demonstrating broad application prospects in agriculture. The culturable microorganisms inhabiting in halophytes and their potential roles in enhancing salt-stress resistance of crops remain limited. This study isolated culturable endophytic bacteria from the roots of two dominant desert halophytes, Haloxylon ammodendron and Halostachys caspica, determined their growth-promoting abilities, and evaluated their capability in improving wheat performance under salt stress. Five saline-alkali tolerant bacterial strains—identified as Priestia endophyticus (S1, Y5), Priestia licheniformis (S2), Streptomyces griseorubens (S7), and Nocardiopsis aegyptia (Y6)—were characterized. These bacterial strains exhibited robust survival in 1.4 mol/L NaCl and high-pH environments (pH > 11.0), while demonstrating multiple growth-promoting traits, including indole-3-acetic acid (IAA) production and inorganic phosphate solubilization. All of the five strains (except for S2) and mixed culture improved the germination potential at 100 mmol/L NaCl. The strains S7, Y5, and mixed culture significantly increased plant height, root length, above ground fresh and dry weight compared to 200 mmol/L NaCl stressed seedlings (200CK)(p < 0.05). Salt stress significantly decreased chlorophyll content by 25.82% and 34.06% under 100 and 200 mmol/L NaCl in comparison to CK. Conversely, PGPE inoculation significantly promoted chlorophyll synthesis of seedlings under salt stress. PGPE inoculation reduced enzyme activities of peroxidase (POD), superoxide dismutase (SOD), and catalase (CAT) relative to the salt stressed seedlings. All inoculation treatments significantly decreased SOD activity by 20.2%–34.62%, and POD activity by 30.79%–53.38%, relative to 200CK. These findings demonstrate that these strains isolated from halophytic plants exhibit positive effects in ameliorating salt stress and improving the growth of wheat seedlings, highlighting their potential for enhancing agricultural productivity in saline-alkali soils.